2004
DOI: 10.1007/s00170-003-1755-2
|View full text |Cite
|
Sign up to set email alerts
|

Design and FEM analysis of the milled groove insert method for cooling of plastic injection moulds

Abstract: During an injection moulding process, it is very difficult to achieve efficient and balanced cooling. It is also difficult to generate an optimal cooling design for industrial parts automatically. In this paper, a milled groove insert method in mould cooling was proposed for cooling of medium and large plastic parts. The advantages of this method include a better cooling effect, ease and flexibility of design, characteristics of auto-design and considerable savings on the coolant flow rate. A household iron pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 18 publications
(21 reference statements)
2
23
0
2
Order By: Relevance
“…6,7 More recently, applying 3-D CAE and 3-D FEM computer-aided simulation have been widely used to investigate the thermal behavior of the cooling system and the configuration of conformal cooling channels. 8,9 These researches' results showed that the conformal cooling channels give a shorter cooling time and better temperature distribution than those of conventional cooling channels. Park and Pham 10 introduced an optimization strategy and investigated some types of conformal cooling layout for an automotive part by applying analytic formulas.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…6,7 More recently, applying 3-D CAE and 3-D FEM computer-aided simulation have been widely used to investigate the thermal behavior of the cooling system and the configuration of conformal cooling channels. 8,9 These researches' results showed that the conformal cooling channels give a shorter cooling time and better temperature distribution than those of conventional cooling channels. Park and Pham 10 introduced an optimization strategy and investigated some types of conformal cooling layout for an automotive part by applying analytic formulas.…”
Section: Introductionmentioning
confidence: 95%
“…Moreover, sensitive analysis, finite element or boundary element coding for optimization of some specific cases are still academic and lack of generalization, so they are inconvenient to apply in reality. On the contrary, some of works 8,9,15 applied 3-D CAE tools to solve the cooling problem for some more complex parts. Yet, the method of reducing the cooling time and optimizing the configuration of conformal cooling channels of these studies were not adequate.…”
Section: Introductionmentioning
confidence: 98%
“…It was reported that cooling quality is better than that of conventional cooling channels. [16][17][18][19][20][21][22][23][24] Along with SFF technique, milled groove conformal cooling channels made by CNC milling machine has also been proposed by Sun Y. F. et al 25,26 Although these kinds of cooling channels offer an even cooling performance, there are still high manufacturing costs for medium and large-sized mold.…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of this new kind of cooling channels for the plastic parts with curved surfaces or free-form surfaces is based on the development of solid free-form fabrication (SFF) technology. On the other hand, conformal cooing channels can also be made by U-shape milled groove using CNC milling machine (Sun et al, 2004). The conformal cooling channels are different from straight-drilled conventional cooling channels.…”
Section: Conformal Cooling Channelsmentioning
confidence: 99%